Adoption mechanisms of a supplier portal: A case study in the European aerospace industry. (November 2019) - Garcia, Fabienne; Grabot, Bernard; Paché, Gilles
Highlights: Adoption mechanisms of supplier web portals in the aerospace industry are studied. A multi-level view is used for a better understanding of the adoption of a supplier web portal. Diffusion of innovations (DOI) factors, network embeddedness in the SC and institutional factors are analyzed. Characteristics of each level need to be jointly activated for a successful adoption. Abstract: This article analyzes the adoption mechanisms of an industry supplier portal, as a specific case of an industry inter-organizational information system (IOIS). Collaborative IOISs have been introduced in many supply chains (SCs) over these last twenty years in order to improve integration and coordination. However, the adoption of such complex IOISs (involving multiple actors and integrating different systems) has often stumbled or failed, leading to unmet expectations. The aim of the research is to highlight the adoption mechanisms of supplier portals by analyzing three main levels: enterprise, SC, and industry. Based on a qualitative case study of AirSupply, the supplier portal developed for the European aerospace industry, the authors show that diffusion of innovations (DOI) factors (enterprise level), network embeddedness (SC level), and institutional factors (industry) may explain the decision to adopt an IOIS. All three of these should be considered to ensure IOIS adoption by the manufacturing organizations. Therefore, they suggest that for successful IOIS adoption, industry IOIS project managers should jointly rely on traditional DOI factors, dense SC networks with numerous ties, and proactive industry institutions.